Origin and Spread of the ALDH2 Glu504Lys Allele - Xiaokai Zhang; Aijun Sun; Junbo Ge (Phenomics, 2021)
Gene polymorphism of acetaldehyde dehydrogenase 2 (ALDH2), a key enzyme for alcohol metabolism in humans, can affect catalytic activity. The ALDH2 Glu504Lys mutant allele has a high-frequency distribution in East Asian populations and has been demonstrated to be associated with an increased risk of cardiovascular disease, stroke, and tumors. Available evidence suggests that the evolution of the ALDH2 gene has been influenced by multiple factors. Random mutations produce Glu504Lys, and genetic drift alters the frequency of this allele; additionally, environmental factors such as hepatitis B virus infection and high-elevation hypoxia affect its frequency through selective effects, ultimately resulting in a high frequency of this allele in East Asian populations. Here, the origin, selection, and spread of the ALDH2 Glu504Lys allele are discussed, and an outlook for further research is proposed to realize a precision medical strategy based on the genetic and environmental variations in ALDH2.